The maternal referral mobile application system for minimizing the risk of childbirth - DIAH INDRIANI (PAGE Press, 2020)
Background: The maternal mortality rate in Surabaya is still quite high due to ineffectice referral health systems. Primary Health Care (PHC) has difficulty referring patients to hospitals which have available resources. The purpose of this study is to develop a mobile app system framework for the maternal referral system. Design and Methods: This study was developed based on the results of the Focus Group Discussion (FGD) with midwives, doc-tors and primary health care heads about the referral system regu-lation in Surabaya City. Results: A mobile app system can be used to communicate patients’ conditions to the hospital. The hospital then will refer back to the PHC as a home care service after the birth. This mobile app has gone through a trial and a development process; it is cur-rently in the process of structuring the mobile app based on the bugs that occur in the system. Conclusions: This mobile app still needs development, espe-cially in minimizing system bugs, and providing faster, more accurate communication.